Four-dimensional metal-organic frameworks - Jack D. Evans; Volodymyr Bon; Irena Senkovska; Hui-Chun Lee; Stefan Kaskel (Nature Communications, 2020)
As the field of metal-organic frameworks is maturing, understanding the dynamics of open frameworks is progressing and rational approaches are under development. Here, the authors outline challenges and potential routes to engineering the spatio-temporal evolution of dynamic metal-organic frameworks.